'Becoming European'? Respatialising the European Schools System through PISA for Schools. Issue 1 (2nd April 2020) - Lewis, Steven
ABSTRACT: This paper examines the Organisation for Economic Cooperation and Development's (OECD) PISA for Schools, a local variant of the more-renowned 'main PISA' test that measures and compares individual school performance on reading, mathematics and science against international schooling systems. Here, I address the governance implications of how PISA for Schools data has been taken up by the transnational European Schools System (ESS). Drawing suggestively across new 'relational' thinking around data-driven modes of governance, as well as interviews with key policy actors within the ESS, I show how PISA for Schools reflects contradictory logics within the ESS, in which the inherently context-based goal of 'becoming European' is juxtaposed with the desire to employ decontextualised international evidence. I conclude by exploring how the perceived need for such data, associated with the global authority of the OECD, can produce a problematic focus on data-driven practices.